UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN METODE ROLE PLAY PADA PELAJARAN IPS KELAS IV SD SWASTA XAVERIUS PADANG SIDIMPUAN - Wesly Silalahi (PGSD Universitas Negeri Medan, 2018)
This research is a classroom action research (PTK) using Role Play learning method as the main target aimed to improve student's learning motivation and to know the difference of students' learning motivation using Role Play learning method with those who do not use Role Play learning method on Science subjects Social on the matter of social problems in the fourth grade of Private Elementary School Xaverius Padangsidimpuan. Thus it can be concluded that the ability of students in understanding the material social problems in Social Science lessons has been motivated in learning.Keywords: Role Play Method, Learning Motivation, IPS Learning.